Inovasi Sektor Publik Dalam Pelayanan Kesehatan Pada Unit Poliklinik Kementrian Sekretariat Negara: Studi Kasus Pada Layanan Aplikasi Chatdoc - Wijoyo Hartono; Ahmad Murodi; Yudi Muhtadi (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
The purpose of this research is to find out the procedures for health services at the Ministry of State Secretariat Polyclinic, find out what are the obstacles in the Ministry of State Secretariat health services and what efforts are being made to overcome these obstacles. The theory used in this study is the theory of five attributes of health care innovation according to Rogers, namely relative advantage, compatibility, complexity, triability, and observability with qualitative methods. Data collection techniques in this study used observation, interviews, and documentation. The results show that health services at the Ministry of State Secretariat using the chatdoc application have good service because with this chatdoc application employees can consult general practitioners and dentists easily and practically, however, there are still some deficiencies, namely the lack of information on laboratory results. still via cellphone or employees come directly to the polyclinic. This chatdoc application continues to provide convenience and comfort for employees at the ministry of state secretariat as much as possible by continuing to update it to add the features needed by employees, doctors and nurses at the ministry of state secretariat.